The Use Superordinate Concept in The Meaning of speech - Dicky Widiya Perkasa; Iman Santoso (IKIP Siliwangi, 2019)
Words have been existed since hundreds of years ago the implicit meaning of a words can indicate an expression of someone Through human words can communicate with various kinds of meanings in their conversation, in the concept of writing the researcher will explain a concept of superordinate which as a form of word level the highest which has the earliest meaning of each word, The good thing that can be learned in this superordinate concept is that the meaning of the word will not become complicated, for example